KEPEMIMPINAN KETUA KELOMPOK TANI, KEDINAMISAN KELOMPOK DAN KEMAMPUAN ANGGOTA DALAM USAHATANI (Jurnal Sains Komunikasi dan Pengembangan Masyarakat [JSKPM], 2020)
ABSTRACTThe leadership of farmers’ group plays a crucial role in boosting the group dynamic as well as the ability of the member. The research aims at analyzing the relations between the leadership of farmers’ groups and the group dynamic and ability of the group member in managing the farm, survey to two farmer’s groups namely Bina Mekarsari and Rawasari was conducted in Purwasari Village, Dramaga District, Bogor Regency. A number of 15 active members from each group were selected as respondents (total farmers involved in the survey were 30)., Interviews with the respondents were administered to gather the data about the leadership and the dynamics of the group. Rank-Spearman Correlation was used to test the correlation between the variables. The research results show that the leadership behaviour and leadership abilities have positive correlation with the level of dynamism of Rawasari Farmers Group. There is no correlation between, leadership styles and the level of group dynamics. However, in Bina Mekarsari Farmer Group, the three leadership indicators do not have correlation with the level of group dynamics. It is also interesting in the two groups, individual characteristics of farmers do not correlate with the group dynamics and also the correlation does not exist between the group dynamics and the ability to manage the farms. This indicates, the leaders of the groups are the centrals for the groups and the members to develop better.Keywords: ability of group members, farmer group, group dynamics, leadershipABSTRAKKepemimpinan kelompok tani memainkan peran penting dalam meningkatkan dinamika kelompok serta kemampuan anggota. Penelitian ini bertujuan menganalisis hubungan antara kepemimpinan kelompok tani, dinamika kelompok dan kemampuan anggota kelompok dalam mengelola pertanian, survei terhadap dua kelompok tani yaitu Bina Mekarsari dan Rawasari dilakukan di Desa Purwasari, Kecamatan Dramaga, Kabupaten Bogor. Sejumlah 15 anggota aktif dari masing-masing kelompok dipilih sebagai responden (jumlah petani yang terlibat dalam survei adalah 30). Wawancara dengan responden diberikan untuk mengumpulkan data tentang kepemimpinan dan dinamika kelompok. Korelasi Rank-Spearman digunakan untuk menguji korelasi antara variabel. Hasil penelitian menunjukkan bahwa perilaku kepemimpinan dan kemampuan kepemimpinan memiliki korelasi positif dengan tingkat dinamika Kelompok Tani Rawasari. Tidak ada korelasi antara gaya kepemimpinan dan tingkat dinamika kelompok. Namun, pada Kelompok Tani Bina Mekarsari, ketiga indikator kepemimpinan tersebut tidak memiliki korelasi dengan tingkat dinamika kelompok. Menariknya pada dua kelompok, karakteristik individu petani tidak berkorelasi dengan dinamika kelompok dan juga tidak ada korelasi antara dinamika kelompok dan kemampuan mengelola pertanian. Ini menunjukkan, pemimpin kelompok adalah pusat bagi kelompok dan anggota untuk berkembang lebih baik.Kata kunci: dinamika kelompok, kelompok tani, kemampuan anggota, kepemimpinan